Empowerment of the export banana sector in decision-making based on data mining for agriculture. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Two farmers’ organization (Grupo Santa Maria and Augura) that represent the banana sector in northern Colombia, with more than 34.560 ha has started to use advanced methods in data collection, analysis for improving climate smart decision-making